FATTY ACIDS IN WILD HEMP SEEDS (Cannabis sativa L. ssp. sativa var. spontanea Vavilov) - Špirović-Trifunović, Bojana; Nedeljković, Dejan; Stojićević, Darko; Božić, Dragana (Acta herbologica, 2021)
Wild hemp (Canabis sativa L. ssp. sativa var. spontanea) is a special variety of industrial hemp (Canabis sativa L. ssp. sativa) which is believed to have originated from the acclimatization of industrial hemp to the conditions of ruderal habitats in Eastern Europe. In the area of ​​Serbia, it is found along roads, on borders, garbage dumps and similar places, but also as a weed in fields. Due to the great popularity of industrial hemp, which can be used for various purposes (raw materials for the food and pharmaceutical industry, production of gluten-free flour, biodiesel, detergents, in folk medicine), many researchers have analyzed its seeds, including analyzes of fatty acids in it. However, there is no data on the presence and composition of fatty acids (whose knowledge can have chemotaxonomic, ecological, evolutionary and nutritional significance) in wild hemp seeds. For the analysis of fatty acids in wild hemp seeds, the seed material was collected from two locations. After extraction with hexane, determination of fatty acid esters was performed by capillary gas chromatography. Chromatographic peaks in the sample were identified by comparing the retention times with the retention times of the fatty acid esters in the analytical standard of a mixture of 37 fatty acid esters. The fatty acid composition is expressed as the relative mass fraction of total fatty acids. The analysis of fatty acids in wild hemp seeds revealed the presence of 15 different acids, with content of 17.5% (U1) and 14.7% (U2) in relation to the total seed weight. Linoleic (45.3 and 47.5%) and α-linoleic (13.6 and 15.5%) acids were the most dominant. Of the 15 detected fatty acids, only 4 are saturated with a representation of about 12%. Unsaturated fatty acids are present in a significantly higher proportion (about 88%), which indicates the nutritional value of this seed.